2014
DOI: 10.4269/ajtmh.14-0081
|View full text |Cite
|
Sign up to set email alerts
|

Field Investigations of Winter Transmission of Eastern Equine Encephalitis Virus in Florida

Abstract: Abstract. Studies investigating winter transmission of Eastern equine encephalitis virus (EEEV) were conducted in Hillsborough County, Florida. The virus was detected in Culiseta melanura and Anopheles quadrimaculatus in February 2012 and 2013, respectively. During the winter months, herons were the most important avian hosts for all mosquito species encountered. In collections carried out in the summer of 2011, blood meals taken from herons were still common, but less frequently encountered than in winter, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 44 publications
3
34
1
Order By: Relevance
“…The findings of this study do align, however, with Bingham et al (2014), who evaluated winter transmission patterns of EEEV in Florida and found that, overall, vector populations were abundant during the winter months and readily feeding. While the data utilized in this paper's research was related to dead-end host fatality, there appears to be an alignment between the habitat suitability predicted by the model and the findings of high activity in the winter months by Bingham et al (2014). This could indicate that EEEV activity in the peak season is partially determined by what the prior winter conditions were.…”
Section: Model Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The findings of this study do align, however, with Bingham et al (2014), who evaluated winter transmission patterns of EEEV in Florida and found that, overall, vector populations were abundant during the winter months and readily feeding. While the data utilized in this paper's research was related to dead-end host fatality, there appears to be an alignment between the habitat suitability predicted by the model and the findings of high activity in the winter months by Bingham et al (2014). This could indicate that EEEV activity in the peak season is partially determined by what the prior winter conditions were.…”
Section: Model Resultssupporting
confidence: 81%
“…The model aligns with previous studies that emphasize the Florida panhandle as a hotspot for EEEV transmission, and this hotspot location has now been verified by both sentinel chicken infection data and equine fatality data. Heberlein-Larson et al (2019) emphasize in their study the theory that Florida represents a region that seeds the virus for transmission in other states in the Northeastbirds migrating through Florida to the Northeast may carry the virus with them, for example, as suggested by Bingham et al (2014). The panhandle, according to the model, represents a series of natural spaces where conditions are optimal not only for spread to avian hosts to continue the epizootic cycle but to equines, which are dead-end hosts where the infection can be fatal.…”
Section: Model Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the range of NA-EEEV, the mosquito Culiseta melanura (Coquillett) is considered the primary enzootic vector of the virus (Howard et al 1988, Komar and Spielman 1994, Armstrong and Andreadis 2010. This mosquito species feeds mainly upon birds (Molaei et al 2006a, Burkett-Cadena et al 2008, Bingham et al 2012, although reptiles (Burkett-Cadena et al 2008) and mammals (Molaei et al 2006b, Bingham et al 2014) may be fed upon in some cases. A number of other mosquito species have been implicated as vectors of EEEV in the southern United States, although mostly as bridge vectors, transmitting the virus from amplification hosts (birds) to dead-end hosts (mammals).…”
mentioning
confidence: 99%